PERANCANGAN DESAIN UI/UX APLIKASI LOWONGAN PEKERJAAN MENGGUNAKAN METODE GOAL DIRECTED DESIGN - Pangiawan, Harfandy Putra; Arianti, Arianti; Musdar, Izmy Alwiah (STMIK KHARISMA Makassar, 2023)
This research aims to design the UI/UX for a job vacancy application using the Goal Directed Design method. Data collection was conducted with 20 respondents who had used the Hi Jobs application, and the data was processed using the System Usability Scale (SUS). Based on the first evaluation using the System Usability Scale (SUS) questionnaire, the average score was 33.5, with Acceptability Ranges receiving the label